Citizen’s Charter in Public Services: Development, Principles and Practice - Rushni Korishi; Buddha Dev Biswas; Mizanur Rahman (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
This paper presents the consequences and development of the citizen’s charters over the decades after their introduction in the United Kingdom (UK) on 22 July 1991. It has used a systematic literature review to organize and present the development process of the citizens’ charter over the years. It does not focus on or target any specific zone or state but is initiated more to connect the links between Commonwealth nations. However, the citizen’s charter is a process to link citizens and public administrators in a more formal/official manner. It has changed a lot over the last three decades. The paper tried to critically investigate the degree of change, development, and practice.